PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN HOTEL FURAYA PEKANBARU - Teti Anggriani Rahayu; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine and analyze the influence of motivation and organizational culture on organizational commitment at Furaya Hotel Pekanbaru. Motivation as a variable (X1), Motivation as a variable (X1), organizational culture as a variable (X2) and organizational commitment as a variable (Y). The method of this research is quantitative descriptive using the SPSS 22 program, where the sample used amounts to 60 employees using accidental sampling techniques and data collection techniques using questionnaires. From the results of analyst data which includes validity test, reliability test, determination test, simple linear regression test and multiple linear regression test, t test, f test so that it can be concluded that Motivation partially has a positive and significant effect on organizational commitment, organizational culture partially influential positive and significant effect on organizational commitment, motivation and organizational culture simultaneously have a significant effect on organizational commitment of Furaya Hotel Pekanbaru employees.Keywords: Motivation, organizational culture, organizational commitment